2021
DOI: 10.3390/ijerph18116043
|View full text |Cite
|
Sign up to set email alerts
|

Diarrhoea among Children Aged under Five Years and Risk Factors in Informal Settlements: A Cross-Sectional Study in Cape Town, South Africa

Abstract: Background: There is limited data on the association between diarrhoea among children aged under five years (U5D) and water use, sanitation, hygiene, and socio-economics factors in low-income communities. The study investigated U5D and the associated risk factors in the Zeekoe catchment in Cape Town, South Africa. Methods: A cross-sectional study was conducted in 707 households in six informal settlements (IS) two formal settlements (FS) (March–June 2017). Results: Most IS households used public taps (74.4%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 39 publications
1
11
2
1
Order By: Relevance
“…The findings are consistent with the 2017 WHO report that 50% of the 2 million deaths worldwide are due to watery diarrhea, 15% persistent diarrhea, and 35% due to dysentery (WHO, 2017). The findings are way higher than that observed in Senegal 26% (range: 7.1-43.6) [11], South Africa 15.3% (range: 8.6-24.2%) [12] and Nepal 40.2% [13]. The observed difference could be because of the study duration where other studies used 2 weeks compared to the one month used in this current study.…”
Section: Discussioncontrasting
confidence: 76%
“…The findings are consistent with the 2017 WHO report that 50% of the 2 million deaths worldwide are due to watery diarrhea, 15% persistent diarrhea, and 35% due to dysentery (WHO, 2017). The findings are way higher than that observed in Senegal 26% (range: 7.1-43.6) [11], South Africa 15.3% (range: 8.6-24.2%) [12] and Nepal 40.2% [13]. The observed difference could be because of the study duration where other studies used 2 weeks compared to the one month used in this current study.…”
Section: Discussioncontrasting
confidence: 76%
“…A recent study, 64 in Cape Town, South Africa, found water sources and storage as a risk factor for diarrhea, likewise other African studies. [65][66][67] We observed that household and shared wells were the most common water source used by residents in the areas served by enrollment primary helath care centers (Supplemental Table 3).…”
Section: Chattaway Et Al (2013)mentioning
confidence: 64%
“…found in a recent study in Cape Town, where a higher prevalence of diarrhoea occurred in children from formal settlements with access to private toilets and piped water compared with informal settlements with access to shared outside toilets and taps. [24] Despite a high number of households sharing the same toilet facility, there was a significantly lower risk of diarrhoea in the study participants.…”
Section: Research Articlementioning
confidence: 81%
“…The extent of the problem is consistent with that in a recent study on diarrhoea in children under 5 years old living in informal and formal settlements in Cape Town. [24] A study undertaken in rural Kenya on animal-related exposures to diarrhoea showed an increased risk of moderate to severe diarrhoea in children exposed to rodent excreta (urine and faeces) outside the house. [25] Exposure of children to rat excreta can result in diarrhoeal disease from Salmonella typhimurium, Escherichia coli and Cryptosporidium parvum.…”
Section: Discussionmentioning
confidence: 99%